The role of the amygdala in the perception of positive emotions: an “intensity detector” - Bonnet, Louise; Comte, Alexandre; Tatu, Laurent; Millot, Jean-louis; Moulin, Thierry; Medeiros de Bustos, Elisabeth (Frontiers in Behavioral Neuroscience, 2015)
Although the development of functional imaging techniques has established the implication of the amygdala in the emotional process, its specific role remains controversial. The aim of this study was to highlight the sensitivity of the amygdala to emotional intensity (arousal). We conducted an analysis of the modulation of amygdala activation according to variation in emotional intensity via an fMRI event-related protocol. Monitoring of electrodermal activity, a marker of psychophysiological emotional perception and which reflects the activation of the autonomic nervous system, was carried out concurrently. Eighteen subjects (10 men; aged from 22 to 29 years) looked at emotionally positive photographs. We demonstrated that the left and right amygdalae were sensitive to changes in emotional intensity, activating more in response to stimuli with higher intensity. Furthermore, electrodermal responses were more frequent for the most intense stimuli, demonstrating the concomitant activation of the autonomic nervous system. These results highlight the sensitivity of the amygdala to the intensity of positively-valenced visual stimuli, and in conjunction with results in the literature on negative emotions, reinforce the role of the amygdala in the perception of intensity.